Clinical Outcomes and Prognostic Markers in Uterine Leiomyosarcoma. Issue 4 (May 2015) - Garcia, Christine; Kubat, Jenna S.; Fulton, Regan S.; Anthony, Adam T.; Combs, Mary; Powell, C. Bethan; Littell, Ramey D.
<x xml:space="preserve">Abstract</x> Objective The aim was to identify clinical parameters and immunohistochemical markers predictive of recurrence and overall survival (OS) in a community cohort of patients with primary uterine leiomyosarcoma (ULMS). Methods/Materials All patients with new diagnosis of ULMS from 1999 to 2007 were identified from the Kaiser Permanente Northern California pathology database. A retrospective chart review was performed to gather demographic and clinical data. The primary outcomes were recurrence-free survival and OS. In addition, a subset of tumor samples was available to analyze 3 immunohistochemical markers using tissue microarray techniques; these are as follows: estrogen receptor (ER) alpha, epidermal growth factor receptor (EGFR), and Ki-67. Results Seventy-five patients with ULMS were identified, of which 63 had adequate tumor tissue available for immunohistochemical evaluation. The median follow-up for all stages was 28 months. The rate of recurrence or progressive disease was 76% for stage I patients compared with 85% for stage II to IV patients. At 3 years, 37% of stage I patients were recurrence free compared with 27% of stage II to IV patients. Overall survival for stage I patients declined from 64% to 38% between 3 and 5 years while remaining stable at 30% for stage II to IV patients. In multivariable analysis, increasing mitotic counts were associated with increased risk of recurrence (hazards ratio [HR], 3.2; P = 0.013) and a trend toward decreased OS (HR, 2.2; P = 0.10). Expression of ER (HR, 1.0), EGFR expression (HR, 1.0), and Ki-67 expression (HR, 1.0) were not predictive of recurrence or OS. Conclusions Recurrence rate of 76% for patients with stage I ULMS was higher than previously published cohorts. Mitotic counts were associated with increased recurrence and decreased OS. Expressions of ER, EGFR, and Ki-67 were not useful for predicting overall recurrence or survival.